2009
DOI: 10.1590/s0100-204x2009000200001
|View full text |Cite
|
Sign up to set email alerts
|

Medidas do grau de precisão experimental em ensaios de competição de cultivares de milho

Abstract: O objetivo deste trabalho foi avaliar a adequação de algumas estatísticas como medidas do grau de precisão experimental, e as relações entre elas. Foram usados os dados de produtividade de grãos de 101 ensaios de competição de cultivares de milho (Zea mays L.), realizados no Estado do Rio Grande do Sul, nos anos agrícolas 2002/2003, 2003/2004 e 2004/2005. Foi estudada a relação entre 12 estatísticas, estimadas para cada ensaio, e as análises de correlação de trilha e de agrupamento foram realizadas com base ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
27

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 8 publications
1
17
0
27
Order By: Relevance
“…The revealed determination coefficients can be considered as high, especially for the genotypic -(0.940), indicating good adjustment of the data to the model used in this research -and phenotypic (0.679) effects. The statistics of the determination coefficient has favorable properties for the classification of the quality of the experiment, along with statistics such as selective accuracy, of the relationship between the coefficients of genetic and experimental variation, heritability (CARGNELUTTI FILHO & STORCK, 2007), where even greater magnitudes of the statistics heritability and coefficient of determination are associated with lower residual variances (CARGNELUTTI FILHO & STORCK, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The revealed determination coefficients can be considered as high, especially for the genotypic -(0.940), indicating good adjustment of the data to the model used in this research -and phenotypic (0.679) effects. The statistics of the determination coefficient has favorable properties for the classification of the quality of the experiment, along with statistics such as selective accuracy, of the relationship between the coefficients of genetic and experimental variation, heritability (CARGNELUTTI FILHO & STORCK, 2007), where even greater magnitudes of the statistics heritability and coefficient of determination are associated with lower residual variances (CARGNELUTTI FILHO & STORCK, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Esses autores consideraram essas estatísticas como adequadas para avaliar a precisão experimental de ensaios de competição de genótipos e estabeleceram faixas de precisão experimental. A ampliação desses estudos foi realizada em conjuntos de 101 ensaios de milho (Cargnelutti Filho & Storck, 2007), 72 ensaios de feijão e 216 ensaios de soja (Cargnelutti Filho et al, 2009b). Todos os estudos foram concordantes e evidenciaram que essas estatísticas, entre outras, como herdabilidade, têm relação direta entre si e são apropriadas para avaliar a precisão experimental de ensaios de competição de genótipos de milho, feijão e soja.…”
Section: Introductionunclassified
“…O dimensionamento do número de repetições adequado para certa precisão, fixada previamente pelo pesquisador, pode ser definido a partir desse conjunto de ensaios, por meio do coeficiente de repetibilidade. Estudos sobre o dimensionamento do número de repetições, com base em estimativas de coeficiente de repetibilidade, obtidas por meio do método da análise de variância (Cruz, 2006), foram realizados em feijão (Cargnelutti Filho et al, 2009a), em soja ) e em milho (Cargnelutti Filho et al, 2010). Ao avaliar a produtividade de grãos dessas culturas, concluiu-se que: ensaios com quatro repetições possibilitam a identificação de cultivares superiores de feijão, com 85% de exatidão no prognóstico de seu valor real (Cargnelutti Filho et al, 2009a); ensaios com quatro repetições e analisados com o método de Papadakis possibilitam a identificação de genótipos superiores de soja, com 80% de precisão ); e ensaios com três e quatro repetições identificam cultivares superiores de milho com, respectivamente, 72,4 e 81% de exatidão no prognóstico de seu valor real (Cargnelutti Filho et al, 2010).…”
Section: Introductionunclassified
“…Furthermore, selective precision as described in RESENDE & DUARTE (2007) can play an important role in experiment quality control. In this sense, CARGNELUTTI FILHO & STORCK (2009), in studying the precision of 101 trials on maize, concluded that the class limits established, based on such statistics as selective precision, heritability coefficient, determination coefficient and F test value for cultivar are adequate for estimating the degree of experimental precision of cultivar competition trials.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent articles (COSTA et al, 2008a;COSTA et al, 2008b;ALVES & RESENDE, 2008;ASSIS et al, 2008;PETEK et al, 2008;CARGNELUTTI FILHO & STORCK, 2009) refer to the selective precision statistic as a measurement of precision or experimental quality for the selection of genotypes.…”
Section: Introductionmentioning
confidence: 99%